How do peer group reflection meetings support medical students’ learning and personal development during clinical rotations? - Valerie van den Eertwegh; Renée E. Stalmeijer (BMC Medical Education, 2023)
Abstract Background Medical schools look to support students in coping with challenges and stressors related to clinical rotations. One potential approach is implementing Intervision Meetings (IM): a peer group reflection method during which students address challenging situations and personal development issues with peers, guided by a coach. Its implementation and perceived effectiveness in undergraduate medical education has however not yet been widely studied and described. This study evaluates how students perceive the effect of a three-year IM-programme during their clinical rotations, and explores which processes and specific factors support students’ personal development and learning during clinical rotations. Methods Using an explanatory Mixed Methodology, medical students participating in IM were asked to evaluate their experiences through a questionnaire at three time points. Questionnaire results were further explored through three focus groups. Data were analysed using descriptive statistics and thematic analysis. Results Three hundred fifty seven questionnaires were filled out by students across the three time points. Students perceived IM to contribute to their ability to cope with challenging situations during clinical rotations. Participants in the focus groups described how IM created an increase in self-awareness by active self-reflection supported by peers and the coach. Sharing and recognizing each other’s’ situations, stories or problems; as well as hearing alternative ways of coping, helped students to put things into perspective and try out alternative ways of thinking or behaving. Conclusions IM can help students to better deal with stressors during clinical rotations and approach challenges as learning opportunities under the right circumstances. It is a potential method medical schools can use to aid their students on their journey of personal and professional development.